Perfecting of a scaling of innovation project’s efficiency - Islamutdinov, Vadim F. (Vysoké učení technické v Brně, Fakulta podnikatelská, 2009)
The strong and feeble sides of the generally accepted methodic of a rating of innovation project’s efficiency based on pure discounted cash flow are considered. The processes of production of entropy in the system of the economic agent are considered. The economic consequences of production of internal and external entropy are uncovered. The paths of perfecting of an existing technique with usage of positions of the theory of systems and thermodynamics are offered. Use of the correction based on economic consequences of production and deduction of entropy during implementation of innovation project is offered.
Keywords: hodnocení efektivity; inovační projekt; entropie; innovation project; entropy; effectiveness evaluation